Kinetic Effects of Temperature and Storage Time on Vitamin C Levels in Lemon Juice : Studi Kinetika Pengaruh Suhu dan Lama Waktu Penyimpanan terhadap Kadar Vitamin C dalam Jus Lemon - Winona Ammadea Gloryani Tapikap; Vika Ayu Devianti (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Lemon (Citrus limon L.) is one of the fruits with the highest vitamin C content. Lemon (Citrus limon L.) is well-known as an ingredient for squeezing and extracting its juice for making beverages. In the process, the vitamin C contained in lemon juice (Citrus limon L.) is easily lost due to oxidation during processing and storage. Therefore, this study aims to determine the effect of storage temperature on vitamin C levels of lemon juice (Citrus limon L.) using UV-Vis spectrophotometry method. This research was conducted experimentally with variations in room temperature and cold storage temperature for 24 hours. The absorbance measurement of the sample was carried out at a wavelength of 265.5 nm. The results showed that variations in storage temperature had an effect on vitamin C levels in lemon juice (Citrus limon L.). The significant value of the F-test was 0.001 and the significant value of the T test at temperature and storage time were 0.02 and 0.000, respectively. The decrease in vitamin C levels followed a zero order kinetic model. Vitamin C levels at cold temperature were lower than room temperature as indicated by the value of the reaction rate constant at cold temperature which was lower than room temperature.